2015
DOI: 10.3233/jhd-150173
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal Diffusion Tensor Imaging Shows Progressive Changes in White Matter in Huntington’s Disease

Abstract: We detected subtle longitudinal white matter changes in early HD patients. Progressive white matter abnormalities in HD may not be uniform throughout the brain, with some areas remaining static in the early symptomatic phase. Longer assessment periods across disease stages will help map this progressive trajectory.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
36
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 35 publications
(38 citation statements)
references
References 82 publications
2
36
0
Order By: Relevance
“…These results are preliminary and require replication in a larger prHD cohort, which may also reveal longitudinal changes in other WM tracts. In addition, our cross‐sectional findings revealed prominent diffusivity abnormalities within certain tracts, most of which show 15‐month changes in early HD . This may suggest that longer time windows are needed to better characterize WM progression in prHD.…”
Section: Discussionmentioning
confidence: 64%
“…These results are preliminary and require replication in a larger prHD cohort, which may also reveal longitudinal changes in other WM tracts. In addition, our cross‐sectional findings revealed prominent diffusivity abnormalities within certain tracts, most of which show 15‐month changes in early HD . This may suggest that longer time windows are needed to better characterize WM progression in prHD.…”
Section: Discussionmentioning
confidence: 64%
“…While research in other neurological disorders such as Parkinson’s [46] and Huntington’s [47] disease have shown that DTI markers of disease can be successfully applied in a mutlicentre study, there have been few studies addressing this issue in SVD. The use of multiple scanners, possibly from different manufacturers, is likely to add noise and may diminish the statistical sensitivity of these metrics.…”
Section: Discussionmentioning
confidence: 99%
“…ROI analysis was then performed for a set of key white matter tracts chosen a priori according to the literature. 7,8,11,27 The ROIs included the corpus callosum (genu, body, splenium), the internal capsules (anterior and posterior limbs), and the external capsules (bilateral internal/external capsules were analyzed jointly to increase the statistical power). To minimize partial volume effects, ROIs were defined by thinning masks from the ICBM-81 white matter atlas 28 by 1mm.…”
Section: Mri Data Analysismentioning
confidence: 99%